1992
DOI: 10.1002/hep.1840150103
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor/hepatopoietin A is expressed in fat-storing cells from rat liver but not myofibroblast-like cells derived from fat-storing cells

Abstract: Hepatocyte growth factor/hepatopoietin A is a complete mitogen for parenchymal liver cells, and its expression is increased as an early response to acute liver injury. To identify the liver cell population responsible for hepatocyte growth factor gene expression, we investigated tissue sections and isolated and purified cell fractions from normal rat liver by in situ and Northern blot hybridization. Hepatocyte growth factor transcripts were present in sinusoidal liver cells, which were preferentially located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(102 citation statements)
references
References 27 publications
11
90
1
Order By: Relevance
“…HGF is expressed well in early cultures of activated primary HSC, although transition of HSC to ␣-SMA-expressing myofibroblast-like phenotype decreases HGF expression. 34 The need for physical disruption of the sinusoidal barrier should be commensurate with the induction of matrix degrading enzymes. During the initial phase of ischemic liver injury, Kupffer cell activation, phagocytic infiltration, and stimulation of sinusoidal endothelial cells, multiple soluble factors and cytokines with HSC-activating properties are released.…”
Section: Discussionmentioning
confidence: 99%
“…HGF is expressed well in early cultures of activated primary HSC, although transition of HSC to ␣-SMA-expressing myofibroblast-like phenotype decreases HGF expression. 34 The need for physical disruption of the sinusoidal barrier should be commensurate with the induction of matrix degrading enzymes. During the initial phase of ischemic liver injury, Kupffer cell activation, phagocytic infiltration, and stimulation of sinusoidal endothelial cells, multiple soluble factors and cytokines with HSC-activating properties are released.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction may occur via several mechanisms. Alison and colleagues 8 have speculated that Ito (or stellate) cells 42 may affect the oval cell response by 1) secreting metalloproteinases 43 specific for basement membrane proteins so that oval cells can invade damaged parenchyma; 2) secreting multiple growth factors [including hepatocyte growth factor 44,45 and transforming growth factor-␤ 39,46 ] to promote oval cell migration and differentiation; 3) creating a microenvironment featuring stromal components that resemble periportal regions, so that oval cells retain biliarylike properties early during regeneration; and 4) synthesizing and secreting laminin chains to stimulate endothelial invasion and sinusoid formation. 47 In addition, our observation that laminin fibers were associated with oval cells may be significant because adhesive interactions between cells and extracellular matrix molecules, including laminin, are proposed to be a critical *The oval cell response was classified by microscopic examination of paraformadehyde-fixed, paraffin-embedded sections stained with hematoxylin and eosin or anti-cytokeratin 19 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…These consist of two chains linked together by disulphide bonds. Recent studies have suggested that HGF is produced by non-parenchymal hepatic cells including Kupffer cells (Noji et al, 1990), endothelial cells (Stoker et al, 1987;Shima et al, 1991), fibroblasts and fat-storing cells in the liver (Ramadori et al, 1992;Schirmacher et al, 1992), endothelial cells in the lung Yanagita et al, 1992). Experimentally, tumour cells are also known to produce HGF; HGF or mRNA encoding this factor has been detected in fibrosarcoma (Stoker et al, 1987), lung cancer (Yoshinaga et al, 1992;Rygaard et al, 1993;Tsao et al, 1993); hepatoma (Miyazaki et al, 1991) and pancreatic cancer cells (Hirota et al, 1993).…”
Section: Methodsmentioning
confidence: 99%